The Rise of Napoleon Bonaparte - Asprey, Robert (New York Basic Books, 2000)
Ever since his untimely death at age fifty-one on the forlorn and windswept island of St. Helena, Napoleon Bonaparte has been depicted as either demi-god or devil incarnate. Now, in The Rise of Napoleon Bonaparte, the first volume of a magisterial two-volume biography, we at last get Napoleon the man. Robert Asprey tells this fascinating, tragic tale in lush narrative detail. He invites the reader to look over Napoleon's shoulder as he dictates decrees and orders; deals with his ungrateful, greedy, unprincipled family; comes into conflict with the royalty of Europe; mingles with the intellectuals, writers, musicians, and actors of the day; leads and inspires his officers and men; and falls in love and fathers children with Josephine, Marie Louise, and various mistresses. The Rise of Napoleon Bonaparte becomes an exciting, reckless thrill ride as Asprey charts Napoleon's vertiginous ascent to fame and the height of power. Here is Napoleon as he was-not saint, not sinner, but a man dedicated to and ultimately devoured by his vision of himself, his empire, and his world.
Include Maps, Illustrations, Bibliography and Index.
Keywords: France -- Emperors -- Napoleon I, Emperor of the French, 1769-1821 -- Generals